PENGARUH KEMAMPUAN KERJA, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BPR SANTI PALA - Anak Agung Istri Laksmi Widyandari; Gde Bayu Surya Parwita; Putu Agus Eka Rismawan (VALUES, 2022)
The purpose of this study was to determine the effect of working ability, motivation of work and work discipline on employee performance at PT. BPR Santi Pala. The population and samples taken were 40 respondents, with the method of saturated sample. Data was collected through questionnaires, documentation studies, observation and interviews. The analysis technique used is multiple linear regression, analysis of determination, and t test. The results show that working ability, motivation of work and work discipline on employee performance partially have a positive and significant effect on employee performance at PT. BPR Santi Pala.